Analysis of The Effect of Credit and Financial Technology on Economic Growth in ASEAN-5 - Firmansyah, Muhammad (Jurnal Riset Ilmu Ekonomi, 2024)
Located at the center of a dynamic economic region, ASEAN-5 countries provide opportunities for each country to improve the socio-economic conditions of its people through developing infrastructure, communication networks, human mobility, and trade in goods and services. Through the provision of credit facilities, the banking sector participates in stimulating investment and economic development. Technological developments in the financial industry and financial technology also influence economic growth. This research measures banking credit service instruments such as third-party funds, investment credit, working capital credit, and financial technology as the level of success in measuring economic growth. This research is quantitative, the analysis technique in this research uses panel data regression to see the influence of the dependent variable on the independent variable. The finding shows that third-party funds, investment credit, and working capital credit significantly affect economic growth. Meanwhile, financial technology does not have a significant effect on economic growth.